Plato's Republic The role of education in Democracy - Berberabe, Darlene Marie (2021)
This paper will take a closer look at how Plato's Republic is relevant in today's world, specifically to education and democracy, and how his very philosophy as represented by dialectic is the essential method of education that will enable and empower the people for democracy. The ability to engage in Socratic elenchus, to stand up to the test of the dialectic, was intended as an exercise in the art of investigating truth, rather than to inculcate any particular set of principles, doctrines, or opinions. For democracy to work, the people in whose hands the power of the state is lodged must be trained in the program that Plato prescribed for the guardians. The curriculum must teach the students courage, the special excellence of the 'spirit' element in their souls, wisdom, the excellence of the 'philosophic' element, and temperance or self-control. Plato's prescription of the training for the guardians in the Academy should very well be adopted for training of the citizenry if they are to be prepared for and capacitated for democracy. It is not just the philosopher-king that is necessary, but more importantly, it is the philosopher-citizen that will make democracy work and that will make democracy meaningful.
Keywords: Plato; Education; Democracy; Dialectic; Dialogue; Educational benefits